Pressure Ulcer Associated with Testicular Prosthesis as a Rare Cause of Spinal Epidural Abscess - Amulya Prakash; Rishi Raj; Aasems Jacob; Douglas Ross (Case Reports in Infectious Diseases)
Spinal epidural abscess is a neurologic emergency with a potential complication to the spinal cord such as paralysis. Frequently, it has a nonspecific initial presentation such as neck or back pain, and hence there is a delay in diagnosis. We present the case of a 60-year-old Caucasian male who presented to emergency room with one week of numbness and weakness of all four extremities. Neurological examination showed variable quadriparesis. Urgent MRI of spine with contrast revealed epidural abscess in the cervical region C4–C6 with resultant cord compression, the underlying etiology for hematogenous spread of infection being pressure ulcer associated with testicular prosthesis. Urgent neurosurgical intervention was done to achieve spinal cord decompression. Both blood and pus cultures were positive for Streptococcus intermedius, requiring prolonged administration of intravenous antibiotics. Clinical outcome was encouraging with progressive gain in motor and sensory function. Spinal epidural abscess is a rare diagnosis; hence, clinicians should have a high index of suspicion for timely diagnosis.